2016
DOI: 10.1590/0103-8478cr20151100
|View full text |Cite
|
Sign up to set email alerts
|

Metazoan parasite of lambari Astyanax altiparanae, collected from the Peixe river, São Paulo, southeast of Brazil

Abstract: In March 2010, 44 specimens of Astyanax altiparanae Garutti & Britski, 2000, commonly

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…The same result was found in the work of Camargo et al (2016). However, in the work of Lizama et al (2008), only the parasite Ascocotyle (A) tenuicollis showed a significant correlation between standard length and abundance and prevalence of parasitism.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The same result was found in the work of Camargo et al (2016). However, in the work of Lizama et al (2008), only the parasite Ascocotyle (A) tenuicollis showed a significant correlation between standard length and abundance and prevalence of parasitism.…”
Section: Discussionsupporting
confidence: 80%
“…This can be explained by the fact that although nine species of parasitic metazoans were found, their abundance were very low. Results differents were obtained in the study of Camargo et al (2016) with A. altiparanae in the Peixe's River, in which 15 species of parasitic metazoan were found and the parasite community was characterized by high richness and low uniformity. Camargo (2015) carried out a study on the seasonal variation of A. altiparanae metazoan parasites collected at another point on the Batalha River on the municipality of Bauru, State of São Paulo, from August 2013 to July 2014 and the results were different from those found in the present study.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…in Psalidodon fasciatus (Cuvier, 1819) (Eiras et al 2010;Luque et al 2013); Acusicola sp., Amplexibranchius bryconis Thatcher & Paredes, 1985, Brasergasilus sp., Ergasilus sp., L. cyprinacea, and Vaigamus sp. in A. lacustris (Gallio et al 2007;Eiras et al 2010;Luque et al 2013;Pádua et al 2015;Camargo et al 2016;Corrêa et al 2016). Thus, the goal of the present study is to report new hosts and new localities for G. euripedesi in the state of Rio Grande do Sul.…”
Section: Introductionmentioning
confidence: 99%
“…The trematode fauna of the two characid species in Brazil includes species from five genera Zonocotyloides Padilha, 1978;Genarchella Travassos, Artigas & Pereira, 1928;Prosorhynchus Odhner, 1905;Prosthenhystera Travassos, 1922;and Halipegus Looss, 1899 and also metacercariae from five genera: Herpetodiplostomum Dubois, 1936;Clinostomum Leidy, 1856;Tylodelphys Diesing, 1850;Ascocotyle Looss, 1899;and Antorchis Linton, 1911 (Thatcher 2006;Kohn et al 2007;Camargo et al 2016). There are also records of unidentified parasites belonging to the family Bucephalidae Poche, 1907(Lizama et al 2008.…”
Section: Introductionmentioning
confidence: 99%